Macroeconomic Stability under Sanctions and Weak State - Arsić, Milojko (Panoeconomicus, 2022)
The inadequate response of the state to the collapse of the monetary system of the former Yugoslavia and the introduction of UN sanctions resulted in one of the longest and largest hyperinflations in economic history. The stabilisation programme, implemented at the end of January 1994, led to an almost immediate halt to hyperinflation, which enabled the recovery of the monetary and fiscal system, the growth of economic activity, and consequently the growth of citizens’ standard of living. The programme had limited economic reach because political actors failed to implement fiscal consolidation, while sanctions made it more difficult to implement economic reforms. After the signing of the Dayton Agreement and the lifting of trade sanctions, Programme II was proposed, containing key measures for the transition from a socialist to a market economy. A coalition of influential interest groups gathered around the ruling parties rejected Programme II, although some ideas from the Programme were implemented in the following years. Keywords: Sanctions, Weak state, Hyperinflation, Macroeconomic stability. JEL: E5, E63, K4, P16.